REVEALING EFL STUDENTS’ RESPONSES ON THE USE OF SOCRATIVE IN READING ACTIVITY - Dewi Nur Suci (Abjadia, 2020)
Industrial Revolution (IR) 4.0 has influenced practice of English Foreign Language (EFL) instruction. One of which is through the deployment of Socrative as the technology integration to enhance the students’ skills of listening, reading, writing and speaking. This paper was aimed at elaborating the use of Socrative in English academic reading classrooms done by students in university level. The students’ responses on their experiences when utilizing this application were revealed. The results exemplified that students used Socrative for reading activities. By collecting the students’ opinions on Socrative via a survey, it was found out that the students could enrich their vocabulary because they employed a reading strategy that should be implemented by them, such as noting difficult word(s), and looking for the meaning in dictionary. In another side, the students argued that this online application had a lack of aspect in a reading course. Further, recommendations on the practice of Socrative in EFL classroom are discussed.